General and Specific Aversive Modulation of Active Avoidance Require Central Amygdala - Kim, Ian T.; Farb, Claudia; Hou, Mian; Prasad, Sunanda; Talley, Elyse; Cook, Savannah; Campese, Vincent D. (Frontiers in Behavioral Neuroscience, 2022)
Three studies provide evidence that the central nucleus of the amygdala, a structure with a well-established role in conditioned freezing, is also required for conditioned facilitation of instrumental avoidance in rats. First, the immediate early gene c-Fos was measured following the presentation of a previously shock-paired tone in subjects trained either on an unsignaled avoidance task or not (in addition to tone only presentations in naïve controls). Significantly elevated expression of c-Fos was found in both the avoidance trained and Pavlovian trained conditions relative to naïve controls (but with no difference between the two trained conditions). In a subsequent study, intracranial infusions of muscimol into the central amygdala significantly attenuated the facilitation of shock-avoidance by a shock-paired Pavlovian cue relative to pre-operative responding. The final study used a virogenetic approach to inhibit the central amygdala prior to testing. This treatment eliminated the transfer of motivational control over shock-avoidance by both a shock-paired Pavlovian stimulus, as well as a cue paired with a perceptually distinct aversive event (i.e., klaxon). These findings provide compelling support for a role of central amygdala in producing aversive Pavlovian-instrumental transfer.